Kelvin, Perry and the age of the earth - England, P; Molnar, P; Richter, F (2007)
The earliest credible account on the age of the Earth came from William Thomson, better known as Lord Kelvin and from his assistant John Perry. They estimated the Earth age by taking into account heat measurements. Kelvin used the Fourier transformation which had shown that diffusion equation, in which the rate of change of temperature at a point is proportional to the second spatial derivative of the temperature, with the constant of proportionality being a property of the material called thermal diffusivity. His initial estimate of the age of the Earth was between 24 million and 400 million years. Geologists now know that the Earth is some 4.5 billion years old. Although using exacting mathematics, the problem is where Kelvin went wrong. Perry discovered the flaw in Kelvin's argument in 1894, and went public in 1895. In Kelvin's model, the thermal gradient near the surface of the Earth drops as the cooled outer skin thickens with age. If the Earth were much older than about 100 million years, this skin would be so thick that the thermal gradient would be much lower than is observed. Perry realized that there is a simple way to stop the skin from thickening: he proposed the heat might be transferred much more efficiently in the interior of the Earth than at the surface. The deep interior could provide a large store of heat and keep the surface temperature high for a long time.